Management of supraerupted maxillary molars in an adult patient using orthodontic miniscrew implants: A pre-prosthodontic therapy - Moina K Adeni; Ratna Parameswaran; Devaki Vijayalakshmi; Savan R Unni (Indian Journal of Dental Research, 2020)
The sequelae of chronic edentulous space is the supraeruption of the opposing teeth which hinders prosthodontic replacement. Molar intrusion of overerupted teeth can be done using miniscrew implants which serves as a promising technique, especially in adult patients. This case report highlights pre-prosthodontic therapy by pure molar intrusion using Temporary Anchorage Device (TAD) in an adult patient seeking prosthesis to enhance chewing efficiency.